THE ROLE OF NON-STANDARD EXPERIMENTS IN IMPROVING THE COMPETENCE OF CHEMISTRY TEACHERS - Togayeva Maftuna Akramovna (Web of Journals Publishing, 2024)
The role of non-standard experiments in improving the competence of teachers in the process of chemistry education is extremely important. The main goal of the educational system is to provide students with theoretical knowledge and to provide the opportunity to apply this knowledge in practice. And non-standard experiments give teachers the opportunity to put their knowledge into practice, develop creative approaches and interact with students.
Keywords: Chemistry, non-standard experiments, traditional educational programs, practice, knowledge, experience, knowledge, pedagogical innovations.